An Analysis Of A Movie “Anna Karenina” According To The Theory Of Literature - Ellen Andriyani; Eryon Eryon (Universitas Muhammadiyah Lampung, 2021)
This research attempts to analyze one of many kinds of literature work namely movie. The purpose of the analysis of this research is to know the intrinsic elements and the relation to one of the literary theories (feminism). There are so many great movies, but in this paper the writer focuses to analyze a movie entitle Anna Karenina. The writer analyzes in the point of view of feminism. The writer interested in feminism because the main characterization of this movie is a woman (Anna Karenina). Anna Karenina lives in Russian at that time. Then this movie tells the brief of Anna Karenina to get her love. The result of this research found that Feminism theory appears in Anna Karenina movie.